Spectroscopic Analysis of DC-Nitrogen Plasma Produced using Copper Electrodes - Ahmed, Ala F.; Yousef, Ali A. (Iraqi Journal of Science, 2021)
This study shows the effects of copper material electrode, applied voltage, and different pressure values on electrical discharge plasma. The purpose of the work is the application of the spectral analysis method to obtain accurate results of nitrogen plasma parameters. By using the optical emission spectroscopy (OES), many N2 molecular spectra peaks appeared in the range from 300 to 480 nm. Also, some additional peaks were recorded, corresponding to atomic and ionic lines for nitrogen, target material, and hydrogen, in all samples. The electron density (ne) was calculated from the measurement of Stark broadening effect, which was found to decrease with increasing pressure from 0.1 mbar to 0.8 mbar. The higher emission intensities occurred at 0.2 mbar working pressure and were reduced with higher pressure. The vibrational temperature (Tvib) for N2 increased from 0.17 to 0.33 eV with increasing the pressure from 0.15 mbar to 0.2 mbar, then decreased to 0.25 eV with increasing the pressure to 0.8 mbar. Other plasma parameters were studied, which are electron temperature (Te), plasma frequency of electron ( ), and Debye length (λD).